Potensi Kewirausahaan Pembelajaran Penerjemahan dan Model Pembelajaran Penerjemahan Berbasisi Kewirausahaan - Akhmad Saifudin (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2018)
This paper aims to describe the entrepreneurial potential that can be attempted in Translation learning and propose a learning model that allows students to achieve professional translator competencies. The results of the discussion show that Translation learning has great potential in the development of entrepreneurship, such as the potential of the profession as a translator, interpreter, and film translator, in terms of financially this profession is also quite promising. The learning model proposed in this study is an internship learning model.